Dosing of Target-Specific Oral Anticoagulants in Special Populations. (September 2015) - Morrill, Amanda M.; Ge, Dan; Willett, Kristine C.
Objective: To review current literature for target-specific oral anticoagulants (TSOACs) and provide critical analysis for dosing recommendations in special population groups.Data Sources: A literature search was conducted in Medline (1996 to April week 2 2015) and Embase (1980 to 2015 week 16) using key terms dabigatran, rivaroxaban, apixaban, edoxaban, kidney diseases, liver diseases, elderly, obesity, and special populations.Study Selection and Data Extraction: Randomized controlled trials in English assessing efficacy and safety of TSOACs in healthy adults and special populations were selected for analysis.Data Synthesis: Phase 3 trials for TSOACs predominately excluded patients with severe renal impairment or active liver disease. There were no exclusion criteria based on age, body weight or body mass index. Additional conclusions were made in special populations, including those with renal or liver impairment and obese and elderly patients, based on secondary analyses, pharmacokinetic, and pharmacodynamic studies.Conclusions: Pharmacokinetic and pharmacodynamic changes associated special populations may alter clinical decision with regard to drug selection and dosing. It is valuable to understand the rationale for labeled dosing recommendations in nonvalvular atrial fibrillation and venous thromboembolism treatment and prevention, particularly in patients that fall into special population groups. Furthermore, the use of TSOACs is likely to increase as clinicians gain experience with these agents and additional TSOACs and indications are approved.